Supporting the Pedagogical Needs of Faculty Teaching Undergraduate Business Students at Kansas State University - Spahr, Kendra; Olsen, Livia (Kansas State University, 2019)
In 2019 Kansas State University was a research site for a large-scale, collaborative study on how academic libraries can best support the pedagogical needs of faculty teaching undergraduate business students. Coordinated by Ithaka S+R, a not-for-profit organization that supports academic communities, the project aimed to answer the questions (1) What are the teaching practices and support needs of instructors of undergraduate business? (2) How can libraries support undergraduate teaching in business? Ithaka S+R published a capstone report based on data from all participating institutions. Researchers at Kansas State University produced this report, based on local data, to identify ways that K-State Libraries can better support undergraduate teaching at K-State’s College of Business Administration.